Effects of corona treatment on the properties of the surface layer of polylactide - Stepczyńska, M.; Żenkiewicz, M. (Polimery, 2014)
The paper investigates the effect of corona discharge (CD) treatment on the properties of surface layer (SL) of polylactide (PLA) film. The modification of PLA was carried out in the air and helium atmosphere and the results were compared on the basis of the assessment of wettability, surface free energy (SFE) calculated using Owens–Wendt method as well as the degree of oxidation (O/C) of the modified SL, determined by photoelectron spectroscopy.